Integrating Geophysical, Geochemical and Geotechnical Characteristics to Assess Soil and Groundwater Resources in Ovade, South-South Nigeria - Uchegbulam, O.; Ugbe, F. C. (Journal of Scientific Research, 2021)
Integrated methods were employed to assess soil and groundwater resources in an oil and gas producing area. Earth resistivity meter was used for the electrical imaging of the subsurface. Physico-chemical, geochemical and geotechnical parameters of soil and groundwater samples were determined. The results of the resistivity data revealed that a high resistive plume with resistivity > 2,000 Ohm-m has penetrated the soil beyond 20 m beneath the surface in some parts. The water samples show mild acidity with pH values in the range 4.3-5.5. Total dissolved solids (TDS) is low 26.55- 38.05 mg/L and conductivity ranges from 55.38-65.60 µS/cm. Iron content in water is fairly high (0.878-0.994 mg/L). Groundwater samples analysis using ultra violet (UV) detector and gas chromatography (GC) show that total petroleum hydrocarbons (TPH) is very low (< 0.01 mg/L and <0.031mg/L) respectively. It can be attributed to the sealing of the confined aquifer by impermeable clay in the case of the groundwater. The average permeability of the soil is 8.098 ´ 10-3cm/s indicating good drainage. The results have shown that shallow boreholes are prone to pollution. Groundwater of the area needs treatment before it can be consumed and integrated methods of investigation should be carried out periodically.